Does Village Fund Have an Impact Toward Economic Growth? - Muhammad Fazri; A. Risdawati Alwi Paluseri; Adelia Oktarina; Dian Karinawati Imron; Febrina Elia Nababan; Cita Pertiwi; Marthella Rivera Roidatua; Yulya Aryani (Economics Development Analysis Journal, 2022)
Indonesia Village Fund policy aims to foster local democracy and rural development through direct funds allocation. During the last seven years (2015-2022), the government has provided Village Fund 400,1 trillion rupiahs (278,3 billion dollars) and continues to increase every year. Numerous studies discover the Village Fund impact on economic conditions but are limited to village scale. This study intends to analyze the impact of the Village Fund on a macro scale, point on the economic growth of a region, specifically on disadvantaged regions. The study conducted through quantitative methods used the panel data approach. The data covers 416 districts from 2015 to 2019. The result shows that the Village Fund has a significant effect, but the value of the effect on GDPR (Gross Domestic Product of Region) is lower than other variables. The effect of Village Fund in disadvantaged regions is greater than in non-disadvantaged regions, which indicates growth acceleration in disadvantaged regions.